Fatty Acid Composition of Five Species of Holothurians from Tropical Waters - Fredalina Basri, Dayang; Abdul Wahab, Khartini (Malaysian Journal of Science, 2003)
Five species of holothuria, Stichopus chloronatus, Stichopus variegatus, Stichopus badionotus, Holothuria atra and Holothuria edulis were collected from the shores and the shelves off Pulau Kapas, Terengganu in Peninsular Malaysia. Their fatty acid composition from the aqueous fraction of PBS and aqueous extracts obtained from connective/muscular tissues were determined using the gas chromatography (GC) technique. A total of 11 fatty acids were analyzed, mainly myristic acid (C 14:0), palmitic acid (C16:0), palmitolic acid (C16:1), stearic acid (C18:0), oleic acid (Cl8:l), linoleic acid (C18:2), arachidic acid (C20:0), eicosapentanoic acid (C20:5), behenic acid (C22:0), erucic acid (C22:l) and docohexanoic acid (C22:6). The main fatty acid components of all the holothuria species in the study were palmitic acid (C16:0), stearic acid (C18:0), oleic acid (C18:1) and eicosapentanoic acid (C20:5) in both fractions and among them, Cl8:0 was the dominant fatty acid. Interestingly, high amounts of C20:5 was found in both the PBS and aqueous fractions of all five species of holothurians investigated. These fatty acid compositions were probably influenced by dietary habits. Further studies are underway at our laboratory to confirm this.